The free speech wars : how did we get here and why does it matter? - Riley, Charlotte Lydia (Manchester University Press, 2021)
"Who gets to exercise free speech, and what happens when powerful voices think they have been silenced? Assembling a diverse group of commentators, activists and academics, this book explores the contemporary free speech wars to try to understand how this issue has become increasingly charged. It asks how the spaces and structures of'speech'- mass media, the lecture theatre, the public event, the political rally and the internet - shape this debate. The contributors examine how acts such as censorship, boycotts, and protests around free speech developed historically and how these histories inform the present. The book explores the opposing sides in this debate: beginning with a defence of speech freedoms and examining how speech has been curbed and controlled, before countering this with an exploration of the way that free speech has been weaponised and deployed as a bad faith argument by people wishing to commit harm. Considering two key battlefields in the free speech wars - the university campus and the internet - this book encourages the reader to be suspicious of the way that this topic is framed in the media today. The free speech wars offers context, provocation, stimulation and - hopefully - a route through this conflict"--Publisher's description